Theatre procedures performed at Knysna Hospital in the Eden district of the Western Cape and their application to post graduate training of family physicians - Du Plessis, D. A. (Stellenbosch : University of Stellenbosch, 2015)
Thesis (MFamMed)--Stellenbosch University, 2014.